(untitled) (Journal of the College of Basic Education, 2023)
Listening has long been the neglected skill in second language acquisition, research, teaching and assessment. However, in recent years there has been an increased focus on L2 listening ability because of its perceived importance in language learning and acquisition. The present study has explored the need of listening comprehension courses in the teacher training programme in the faculty of education in Hodeidah university. After one semester training in listening, the researcher used an IELTS test as an authentic speech to test the level of second year students in the faculty of education. The statistical analysis of the results provided some evidence in support of the need of listening comprehension in the training courses of teachers in the English department of the faculty of education in Hodeidah university.